Structuralism and Religious Values in Zainul Muttaqin’s Short Story ’Surga Ada di Rumah’: A Robert Stanton Perspective - Neisyiah, Devana Nur (Maliki Interdisciplinary Journal, 2024)
This study analyzes the structural elements and religious values ​​in the short story "Surga Ada di Rumah" by Zainul Muttaqin through the perspective of Robert Stanton’s structuralism. Religious values, especially the values ​​of faith, worship, and morals, are analyzed by looking at the analysis of structural elements such as plot, characterization, and setting expressed in the short story. Mustopa, the main character, is described as a figure full of ambition to go to Mecca to perform the hajj, which ultimately causes him to neglect his moral responsibility towards his mother, until he realizes that heaven is actually under his mother’s feet. This analysis shows that the structural elements in the short story not only build a narrative but also convey moral and religious messages to the reader. This study has contributed to providing an understanding of literature functioning as a medium to convey religious values ​​through the interaction of structural elements.